Unraveling the Language Play on YouTube: A Sociolinguistic Study of Code Choice in Online Content - Wibowo, Hanafi; Anisah, Siti (STAIN Majene, 2025)
The use of code mixing and code switching is one of the exciting phenomena in social media. This research aims to identify the types of code switching and code mixing and to determine the reasons behind code switching and code mixing in this content. The method of this research employed a qualitative descriptive design. The data of this research were taken from the video “Daniel Tetangga Kamu” with Dewi Sandra's guests for parts 1-3, which focused on the code mixing and switching and the reasons for code mixing and switching between them. In collecting the data, the researcher observes the video, makes a transcription of the recorded data and organizes it into written data, and then classifies it based on the categories. The results showed that the most dominant type of code mixing found on the Daniel Mananta Network is the insertion of words. While the most dominant type of code switching was Intra-sententia, the research revealed that the reasons why the speaker uses code mixing and switching in their conversation were to talk about a particular topic, quoting somebody else, being emphatic about something, switching as an interjection, repetition, clarifying and expressing status of group identity. The implication of this research contributes to revealing that code mixing and code switching were not only prevalent but also serve various communicative functions, reflecting the nuanced ways in which language was used in the context of the YouTube Channel. The insights gained from this research offer valuable implications